Nodal tuberculosis revisited: a review - Uma Handa; Irneet Mundi; Sugandha Mohan (Journal of Infection in Developing Countries)
Lymphadenitis is the most common extrapulmonary manifestation of tuberculosis. Tuberculous lymphadenitis is considered to be the local manifestation of the systemic disease, whereas lymphadenitis due to nontuberculous mycobacteria is truly a localized disease. A high index of suspicion is needed for the diagnosis of tuberculous lymphadenitis which is known to mimic a number of pathological conditions. Over the last two to three decades, fine needle aspiration cytology (FNAC) has emerged as a simple out-patient diagnostic procedure for the evaluation of tuberculous lymphadenitis and has replaced lymph node biopsy for histopathology. A number of molecular methods have also been introduced in diagnostics which have greatly improved the diagnostic accuracy. This article provides a review of epidemiology, clinical manifestations, and pathogenesis and emphasizes current trends in pathologic diagnosis of nodal tuberculosis.